FAKTOR DETERMINAN KEJADIAN DIABETES MELITUS - Holis Tiawati; Thresya Febrianti (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Background: Diabetes mellitus is a non-communicable disease that increases every year and causes many losses for sufferers and the health financing sector due to complications such as heart and blood vessel problems, stroke, kidney failure, vision problems, leg amputations, and nerve damage. Objective : This research was conducted to analyze the risk factors associated with the incidence of Diabetes Mellitus in the UPT Puskesmas Parung Work Area. Methods: This research is an analytical study using a case control design. The sample cases in the study were respondents who were diabetes mellitus sufferers, namely 69 people and control samples was 6 people who were not diabete melitus sufferers. The sampling technique used in this study (total sampling) for the case group and simple random sampling for the control group. The results showed that there was a significant relationship between physical activity with the incidence of  diabetes mellitus (p value = 0,004; OR = 2,947 (95% CI 1.469-5.912)). Meanwhile smoking behavior and consumption of fruits and vegetables did not have  a significant relationship with the incidence of diabetes melitus (p value>0.05). Conclusion: Public health center officers need to maximize efforts to educate the case groups or control groups regarding risk factor control such as physical activity and consumption of fruits and vegetables